El juego por rincones para el desarrollo del pensamiento creativo de las niñas y niños del subnivel inicial II de 4 a 5 años del colegio de bachillerato particular San Gerardo de la ciudad de Loja. Periodo lectivo 2014 – 2015 - Arévalo Luzuriaga, Liliana del Rocío (2016)
This study is titled: Play corners for the development of creative thinking in girls and boys at the early childhood education level Inicial II between the ages of 4 and 5 at the Colegio de Bachillerato Particular San Gerardo School in the city of Loja during the 2014-2015 school year. The main objective of the study is to evaluate the importance of play corners as a tool for developing creative thinking for boys and girls in the early childhood education level Inicial II from 4 to 5 years of age with the hope of better appreciating this tool in relation to the challenge of developing creative thinking. To these ends, the following methods have been used in this study: the scientific method, deductive reasoning, inductive reasoning, description, and statistical analysis. Data was collected using observation rubrics to verify behavior, qualities, use of materials and use of play corners by children; as well as through interviews with teachers to gain information about conduct and growth on the part of children who use the play corners; and finally, activities were used, which favor the development of creative thinking. Our study sample came from two classrooms: one, “gray bunnies” with 11 girls and 10 boys and the other, “brown bunnies” with 10 girls and 10 boys for a total study sample of 21 girls and 20 boys. The teacher interviews revealed that teachers at Colegio de Bachillerato Particular San Gerardo School understand creative thinking and also know how to employ play corners, as these are part of the methodology of the institution. The observation guide revealed that a high percentage of children demonstrated creativity in the play corners and used cooperation. The observation guide also revealed that more than half of the play corners are satisfactory for developing creativity.